Participación de la familia en el proceso educativo de las y los estudiantes del séptimo “A” de educación básica de la escuela “Teniente Hugo Ortiz” sección vespertina de la ciudad de Loja y la intervención del Trabajador Social - Suquilanda Agurto, Narcisa de Jesús (2020)
This work called "PARTICIPATION OF THE FAMILY IN THE EDUCATIONAL PROCESS OF THE STUDENTS OF THE SEVENTH" A "OF BASIC EDUCATION OF THE SCHOOL" TENIENTE HUGO ORTIZ "VESPERTINA SECTION OF THE CITY OF LOJA AND THE INTERVENTION OF THE SOCIAL WORKER" to one of the many problems that affects the educational environment. The field research exposes the relevant data through the quantitative interpretation and qualitative analysis, which allowed to support the object of study formulated in the scientific question "What are the factors that Influences the Family Participation in the Educational Process of the Students". In the same way, the objectives set out in the research could be fulfilled, such as the general objective of knowing the factors that influence family participation in the educational process of the students of the Teniente Hugo Ortiz School in the afternoon section of the city of Loja, to strengthen family participation in this area through a proposal for social action; and the specific objectives To diagnose on a scientific theoretical basis the family participation within the educational process of the students and to analyze causes and effects and possible consequences that the family participation generates within the educational process on the students. The methodology used in the research was based on the scientific method with the application of the inductive method, deductive method, statistical method, synthetic method and analytical method, the techniques to use the semi-structured interview, survey, observation and observation guide tools, guide questions, through which the most relevant information was gathered, which reveals the absence of family participation in the educational process of the students 9 The results answered the scientific question, in which a decreased participation of the family in the educational process was determined, the family was disconnected from school activities, parents were discouraged from participating in activities that strengthened the relationship. of the educational trilogy, allowing to propose a proposal that strengthens the participation of the family in the educational process in the students, from an intervention approach from Social Work, that sensitizes on this problem.